Non-Digestible Oligosaccharides Can Suppress Basophil Degranulation in Whole Blood of Peanut-Allergic Patients - Hayen, Simone M.; den Hartog Jager, Constance F.; Knulst, André C.; Knol, Edward F.; Garssen, Johan; Willemsen, Linette E. M.; Otten, Henny G. (Frontiers in Immunology, 2018)
Background: Dietary non-digestible oligosaccharides (NDOs) have a protective effect against allergic manifestations in children at risk. Dietary intervention with NDOs promotes the colonization of beneficial bacteria in the gut and enhances serum galectin-9 levels in mice and atopic children. Next to this, NDOs also directly affect immune cells and low amounts may reach the blood. We investigated whether pre-incubation of whole blood from peanut-allergic patients with NDOs or galectin-9 can affect basophil degranulation. Methods: Heparinized blood samples from 15 peanut-allergic adult patients were pre-incubated with a mixture of short-chain galacto-oligosaccharides and long-chain fructo-oligosaccharides (scGOS/lcFOS), scFOS/lcFOS, or galectin-9 (1 or 5 μg/ml) at 37°C in the presence of IL-3 (0.75ng/ml). After 2, 6 or 24 hours, a basophil activation test (BAT) was performed. Expression of FcεRI on basophils, plasma cytokine and chemokine concentrations before degranulation were determined after 24 hours. Results: Pre-incubation with scGOS/lcFOS, scFOS/lcFOS or galectin-9 reduced anti-IgE mediated basophil degranulation. scFOS/lcFOS or 5μg/mL galectin-9 also decreased peanut-specific basophil degranulation by approximately 20%, mainly in whole blood from female patients. Inhibitory effects were not related to diminished FcεRI expression on basophils. Galectin-9 was increased in plasma after pre-incubation with scGOS/lcFOS, and both NDOs and 5μg/mL galectin-9 increased MCP-1 production. Conclusion & Clinical relevance: The prebiotic mixture scFOS/lcFOS and galectin-9 can contribute to decreased degranulation of basophils in vitro in peanut-allergic patients. The exact mechanism needs to be elucidated, but these NDOs might be useful in reducing allergic symptoms.